Human papillomaviruses in Western Africa: prevalences and risk factors in Burkina Faso - Hatzipanagiotou, Maria Eleni; Holzinger, Dana; Millogo, Françoise; Pawlita, Michael; Wacker, Jürgen (Archives of gynecology and obstetrics, 2018)
PurposeCervical cancer is the most common cancer in women in low income countries. Certain oncogenic types of human papillomaviruses are causally associated with the cervical cancer. To ensure effective primary prevention through the introduction of a national vaccination program in Burkina Faso, information about the disease burden of HPV infection in the country is of great importance.MethodsIn the present work the prevalence of 54 different HPV types and 18 other sexually transmitted infection as well as the predominant risk factors for the development of cervical cancer were investigated in Ouagadougou. A cross-sectional study on two populations without (n=471) and with known cervical dysplasia (n=39) was carried out between October 2013 and March 2014. Retrospectively, data on possible and secured risk factors of the cervical carcinoma were collected. The participants were examined gynecologically and a vaginal lavage was taken, which was molecular genetically examined for 54 different human papillomavirus genotypes and 18 other STIs.ResultsThe prevalence of human papillomavirus was 42.3% (188/444) in the first study population and 87.2% (34/39) in the second study population. The immunization coverage would be 24.5% of the HPV types and 33.9% of the high-risk HPV types with quadrivalent vaccine Gardasil®. The nonavalent vaccine Gardasil®9 (9vHPV) would cover 37.3% of all HPV types and 57.1% of high-risk HPV types. ConclusionThe prevention of infection with human papillomaviruses by vaccination is expected to result in a drastic reduction in the morbidity and mortality of the cervical cancer in Burkina Faso.